ORGANISASI PEMBELAJARAN, KOMPETENSI DAN KINERJA KARYAWAN BANK BRI DI JAKARTA - Rahardjo, Thea H. (Jurnal Ekonomi, 2016)
His study aimed to determine empirically the retail mix in small business retail, that includes Physical Facilities Merchandising, pricing, promotion, services and Organization/Personil, as a predictor of the performance of small retail businesses and competitive advantage. The method used in sampling was purposive sampling, a total of280  respondents  drawn  at  small  retail  businesses  in  Tangerang.  The  data  analysis technique used is Structural Equation Modeling (SEM), using by LISREL versi 8.8 are need to test the hypothesis. The results showed, retail mix small business strategy that includes Physical Facilities Merchandising, services and Organization/Personil can be used to predict the performance of retail, which means that the research hypothesis tested. While  pricing,  promotion  can  not  be  used  to  predict  the  performance  of  retail. Furthermore, the  retail  business  performance  can  be used  to  predict  the competitive advantage.  Through  these  results  can  be  material  for  the  attention  of  small  retail businesses to keep improving the combination of retail mix, either already affect or not affect the performance of the business, because through good performance can affect the competitive advantage for retailers in running the business.